Using an optimisation strategy to design a supercritical CO2 radial inflow turbine transonic stator. Issue 1 (31st December 2022) - Qi, Jianhui; Ma, Bingkun; Qin, Kan; Han, Kuihua; Liu, Jiangwei; Xu, Jinliang; Yang, Yueming; Xiao, Yongqing; Wang, Xujiang
Abstract : During the operation of supercritical CO 2 (sCO 2 ) radial inflow turbines (RITs), sonic conditions may happen, which will decrease their efficiency. Non-standard design geometries are needed to reduce the losses. However, modifying the turbine geometry is a challenge, especially as the optimum shape may be non-intuitive; commercial computational fluid dynamics (CFD) software is not friendly towards automation by surrogate scripts, and the traditional design method for blade passage shape is not suited to the optimisation of aerodynamic turbine design. Hence, in this study, a stator nozzle for a 120 kW sCO 2 RIT, whose geometries are obtained from in-house preliminary design code TOPGEN t m, has been optimised with a modularised geometry optimiser. To parametrise the geometry, a parametrised stator mesh generator based on a meridional streamline is developed. Bulk CFD simulations are carried out with OpenFOAM ®, to form a Pareto front with a vector of 14 variables. Three final stators have been selected: they are the optimised Mach number distribution ( σ M ), the optimised outlet flow angle distribution ( σ α ) and a compromise case. The the outlet boundary properties of these stators are extracted and discussed. The optimised σ M case has the shortest divergent nozzle, returns the best σ M and the least loss; the optimised σ α case has the longest divergent nozzle and returns a better-uniformed outlet flow; the compromise case has the medium length of the divergent case. All these stators have fixed mass flow rates to allow de-coupling of the upstream system from the rotor. This study will ultimately benefit the development of the sCO 2 power cycle.